2022
DOI: 10.1002/jbt.23010
|View full text |Cite
|
Sign up to set email alerts
|

Sodium benzoate induces neurobehavioral deficits and brain oxido‐inflammatory stress in male Wistar rats: Ameliorative role of ascorbic acid

Abstract: Background: Sodium benzoate (SB) is a widely used food preservative. However, excessive intake of a high dose of SB poses a risk of neurotoxicity. Ascorbic acid (AA) is a naturally occurring antioxidant found in fruits with reported neuroprotective properties. The present study investigated the neurobehavioral and biochemical alterations in SB-treated rats and the ameliorative effect of AA in rats.Methods: Forty-two male Wistar rats were divided into six groups (n = 7). Group 1 (vehicle, 10 ml/kg), Groups 2-4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 67 publications
0
0
0
2
Order By: Relevance
“…Однією з найпоширеніших хімічних речовин з антимікробними властивостями, яку часто використовують у харчовій промисловості, є бензоат натрію [1]. Це сіль бензойної кислоти, котру застосовують як консервант не лише у харчових продуктах, але й під час виробництва ліків, косметичних сумішей та шампуней [2]. Відповідно до офіційної публікації Всесвітньої організації охорони здоров'я (ВООЗ) [3] застосування бензоату натрію в харчовій промисловості обмежено до 0,1%, а допустима добова норма цього консерванта становить 5 мг/кг на добу.…”
Section: вступunclassified
“…Однією з найпоширеніших хімічних речовин з антимікробними властивостями, яку часто використовують у харчовій промисловості, є бензоат натрію [1]. Це сіль бензойної кислоти, котру застосовують як консервант не лише у харчових продуктах, але й під час виробництва ліків, косметичних сумішей та шампуней [2]. Відповідно до офіційної публікації Всесвітньої організації охорони здоров'я (ВООЗ) [3] застосування бензоату натрію в харчовій промисловості обмежено до 0,1%, а допустима добова норма цього консерванта становить 5 мг/кг на добу.…”
Section: вступunclassified
“…Its strong solubility in water and good stability has led to its widespread use in a variety of food products, including margarine, sauce, marmalade, gelatin, liqueurs, beer, fruit juice, and soft drinks (Bruna et al, 2018). Asejeje et al, (2022) reported that SB is generally recognized as safe (GRAS) by the Food and Drug Administration (FDA, 1991), with a 0.1% (1000 ppm) permissible limit level in food. Additionally, at dosages of 647-825 mg/kg of body weight per day, the International Program on Chemical Safety (IPCS) revealed no significant health effects in humans (Noorafshan et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…У продукти харчування все частіше додають різноманітні хімічні речовини з антимікробними властивостями -консерванти, серед яких чільне місце займає бензойна кислота та її похідні (Piper et al, 2017). Сьогодні як консервант часто використовують бензоат натрію (натрієва сіль бензойної кислоти), який маркується як Е211 (Asejeje et al, 2022). В організмі бензоат натрію може окиснюватися та проявляти мутагенний, тератогенний, прооксидантний впливи (Oloye et al, 2022).…”
unclassified